RESPONSE POSTHARVEST QUALITY OF POMEGRANATES TO THERMAL TREATMENTS, IMMERSING IN BLACK SEED AND FLAXSEED OILS - Aljabary, Ali Muhi Aldeen Omar; Fatih, A.A.; Ahmad, Z. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was carried out to investigate  thermal treatments, immersing in black seed and flaxseed oils on postharvest quality pomegranate fruits cv. Salakhan . Fruits were randomly divided into two experiments: First, thermal treatment by which fruits are immersed for four minutes at 25, 40 and 50°C in hot water (HW), and fruits are exposed to hot air (HA) for one hour at 40 and 50°C plus control treatment. Second, fruits are immersed for 4 minutes in 1 and 2% for the black seed and flaxseed oil, plus control treatment. Then, fruits are placed in the storage at 5±1 ºC and 85-95% of relative humidity for four months. Both experiments performed by using Complete Randomize Design. The results were indicated that soaking fruits in HW for four minutes at 40°C significantly decreased the weight loss and physiological disorder, whilst significantly increased most of studied attributes compared to control. However, HA treatments exposure for 1 hour at 40 and 50°C, with increasing in the HA levels, decreased the weight loss and physiological disorder, but increased some of studied attributes compared to control. Moreover, the immersing fruits in 1% black seed or 1% flaxseed oil significantly reduced weight loss and physiological disorder. In addition, the immersing fruits in 1% flaxseed oil lead significantly increased most of studied attributes compared to control.